The Radiographic Findings of Congenital Facial Infiltrating Lipomatosis: A Case Report - Hoorieh Bashizadehfakhar; Mehrdad Panjnoush; Yasaman Kheirandish; Azin Sedaghati; Faeze Mirjalili; Sara Aliasghari (Tehran University of Medical Sciences, 2022)
Congenital diffuse infiltrating lipomatosis of the face (CDIL-F) is a rare clinicopathological entity with an unknown etiology, in which mature adipose tissue infiltrates the soft tissue structures in one side, and causes considerable asymmetry. Herein, we report a case of CDIL-F who underwent many surgical procedures without definite diagnosis during 12 years.  CDIL-F presents symptoms with various severity levels due to infiltration of adipose tissue that makes removal difficult. Thus, it is recommended to inform patients about the high rate of recurrence.